Model Design of Helical Type Vertical Shaft Wind Turbine with Capacity of 5 W - Achdi, Endang; Syahbardia, Syahbardia; Rusdianto, Fadhilah Fahmi (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2023)
A vertical axis wind turbine (VAWT) is a power generator that uses wind power to generate torque. The VAWT can be pointed in any direction, meaning it doesn't need to be pointed into the wind to generate power. Thus, there is potential for large power plants using VAWTs as their size can be significantly increased. However, there are also some drawbacks to the VAWT. VAWT has the characteristics of self-starting. But still, an additional power source is needed to start the turbine rotation until a certain rotation speed is reached or it must operate at high wind speeds. The main objective of our work is to create a 5 W VAWT model (helical type) to optimize self-starting of vertical axis wind turbines. The outline of this report is regarding the design of our VAWT model, which will have self-starting characteristics. To increase the self-starting status, our efforts are to optimize the type, dimensions and material of the turbine blades. We also optimized the rotor dimensions. As a result, a model helical three-blade turbine was built and tested. The blade turbine made of composites has been balanced with the rotor prior to testing. The test uses 2 fans with a speed of 3-5m/s, the test is carried out to obtain wind turbine performance data.